The Effects of Micro Finance Institutions on Financial Management Practices in Households in Kayunga District - Godfrey Adriko (Uganda Christian University, 2026)
This research was conducted to find out the effects of micro finance institutions on financial management practices in households in Kayunga district. The researcher carried out the study by moving to a few selected households from Kayunga Town Council to the Bbaale Constituency. Households in Kayunga district have access to capital to expand their business, 14% of the respondents strongly disagreed, 26% of the respondents disagreed, 10% of the respondents were not sure, 20% of the respondents agreed and 30% of the respondents strongly agreed. In addition borrowed funds are invested in income generating projects, 48% of the respondents strongly disagreed, 6% of the respondents disagreed, 14% of the respondents were not sure, 20% of the respondents agreed and 12% of the respondents strongly agreed. Borrowed funds are invested in asset accumulation, 14% of the respondents strongly disagreed, 26% of the respondents disagreed, 8% of the respondents were not sure, 32% of the respondents agreed and 20% of the respondents strongly agreed. So based on the results collected, most respondents agreed that borrowed funds are invested in asset accumulation by households. Participation in MFIs activities has increased saving rates in households in Kayunga district, 10% of the respondents strongly disagreed, 20% of the respondents disagreed, 6% of the respondents were not sure, 34% of the respondents agreed and 30% of the respondents strongly agreed. Savings groups with accounts in MFIs contribute social capital to support households in problems, 22% of the respondents strongly disagreed, 10% of the respondents disagreed, 38% of the respondents were not sure, 20% of the respondents agreed and 20% of the respondents strongly agreed. According to that information, the lowest portion of respondents disagreed with the statement that saving groups with accounts in MFIs contribute social capital to support households in problems. Bookkeeping provides clear records of borrowed finances to ensure proper accountability, 4% of the respondents strongly disagreed, 16% of the respondents disagreed, 16% of the respondents were not sure, 34% of the respondents agreed and 30% of the respondents strongly agreed. Based on the results, the respondents tentatively agreed that MFIs provides clear records of borrowed finances to ensure proper accountability. Establish clear financial goals, conduct thorough research, utilize employer benefits, focus on low-interest borrowing options, diversify investment, monitor and adjust investment strategies, build an emergency fund and seek professional financial advice, are some of the suggested measures that can improve ways of investing finances by households in Kayunga district. Diversification of financial products, enhanced financial literacy programs, use of technology for accessibility, incentives for savings, community-based savings group, regular monitoring and feedback, collaboration with local organizations and focusing on social impact measurement are some of the suggested measures to improve the performance of microfinance institutions on financial savings practices in households in Kayunga district. Forster a culture of financial literacy, integrate bookkeeping with loan products, regular monitoring and feedback, create incentives for good bookkeeping, offer personalized financial counselling, implement group-based learning, provide training and workshop and develop user-friendly financial tools are measures on how microfinance institutions can improve on book keeping practices in households in Kayunga district.
Undergraduate